Electrophilic Sulfoximidations of Thiols by Hypervalent Iodine Reagents - Wang, Han; Zhang, Duo; Cao, Mengwei; Bolm, Carsten (Synthesis, 2019)
A new electrophilic sulfoximidation of thiols has been developed. Using sodium hydride as a base, the treatment of sulfoximidoyl-containing hypervalent iodine(III) reagents with thiols affords the corresponding N-sulfenylsulfoximines (N-thiosulfoximines) in good to excellent yields. A plausible mechanism is proposed.
Keywords: sulfoximidation; thiol; N-sulfenylsulfoximine; hypervalent iodine reagents; ligand exchange